2010
DOI: 10.1038/emboj.2010.203
|View full text |Cite
|
Sign up to set email alerts
|

Disulphide production by Ero1α–PDI relay is rapid and effectively regulated

Abstract: The molecular networks that control endoplasmic reticulum (ER) redox conditions in mammalian cells are incompletely understood. Here, we show that after reductive challenge the ER steady-state disulphide content is restored on a time scale of seconds. Both the oxidase Ero1α and the oxidoreductase protein disulphide isomerase (PDI) strongly contribute to the rapid recovery kinetics, but experiments in ERO1-deficient cells indicate the existence of parallel pathways for disulphide generation. We find PDI to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
139
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 59 publications
10
139
0
Order By: Relevance
“…or by oxidized PDI, resulting in decreased Ero1 activity (18,22,24,25). Although this feedback regulation model has been widely accepted, our present studies have unraveled unique features of the yeast Ero1p-Pdi1p interplay, which are very different from the human Ero1␣-PDI system but were neglected in previous studies.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…or by oxidized PDI, resulting in decreased Ero1 activity (18,22,24,25). Although this feedback regulation model has been widely accepted, our present studies have unraveled unique features of the yeast Ero1p-Pdi1p interplay, which are very different from the human Ero1␣-PDI system but were neglected in previous studies.…”
Section: Discussionmentioning
confidence: 67%
“…It has been found that human PDI reduces and also re-oxidizes the regulatory disulfides of Ero1␣ very fast (18), whereas yeast Pdi1p is more potent to inhibit Ero1p than to activate Ero1p (25). Coincidently, in cells endogenous Ero1␣ exists in mixed states of oxidized and semioxidized (24,27), whereas Ero1p is almost fully oxidized (25).…”
mentioning
confidence: 99%
“…eukaryotes, is now thought to be the oxidative engine that serves as the primary oxidase of PDI (Appenzeller-Herzog et al 2010). Concomitantly, hydrogen peroxide (H 2 O 2 ) is thought to be produced from oxygen as an electron acceptor (Enyedi et al 2010).…”
Section: Er Redox Homeostasismentioning
confidence: 99%
“…Pdi1p was observed in vitro [22], and this phenomenon has been also demonstrated in Ero1-deficient cells as a possible alternative pathway for disulfide bond generation [36]. These findings suggest that the fine tuning of luminal redox homeostasis involves a direct thiol/disulfide exchange between GSH/GSSG and PDI, which also recycles the oxidizing power of GSSG into the machinery of oxidative folding [37].…”
mentioning
confidence: 89%